Preferences for and against stimuli paired with food - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1999)
Pigeons were presented with a concurrent-chains schedule in which terminal-link entries were assigned to two response keys on a percentage basis. The terminal links were fixed delays that sometimes ended with food and sometimes did not. In most conditions, 80% of the terminal links were assigned to one key, but a smaller percentage of the terminal links ended with food for this key, so the number of food reinforcers delivered by the two alternatives was equal. When the same terminal-link stimuli (orange houselights) were used for both alternatives, the pigeons showed a preference for whichever alternative delivered more frequent terminal links. When different terminal-link stimuli (green vs. red houselights) were used for the two alternatives, the pigeons showed a preference for whichever alternative delivered fewer terminal links when terminal-link durations were long, and no systematic preferences when terminal-link durations were short. This pattern of results was consistent with the predictions of Grace's (1994) contextual choice model. Preference for the alternative that delivered more frequent terminal links was usually stronger in the first few sessions of a condition than at the end of a condition, suggesting that the conditioned reinforcing effect of the additional terminal-link presentations was, in part, transitory.
Keywords: *Choice Behavior/ph [Physiology]; *Feeding Behavior/px [Psychology]; *Food Preferences; Animals; Behavior, Animal; Behavior, Animal/ph [Physiology]; Choice; Choice Behavior; Columbidae; Concurrent chains; Conditioned reinforcement; Conditioning (Psychology); Conditioning, Psychological; Feeding Behavior; Food Preferences; Key peck; Pigeons; Reinforcement (Psychology); Reinforcement probability; Reinforcement, Psychology; animal; animal behavior; article; conditioning; decision making; dept.psy; feeding behavior; food preference; physiology; pigeons and doves; psychological aspect; reinforcement